Actualización de la distribución de Rhamdella aymarae (Siluriformes: Heptapteridae) - Briñoccoli, Yanina Florencia (2018)
The genus Rhamdella is included in the family Heptapteridae and comprises six species distributed in Argentina, Brazil and Bolivia. Rhamdella aymarae was originally described from the Itiyuro River, an arheic basin in the North of Salta, Argentina. According to a proposed phylogenetic based on morphological characters, R. aymarae and R. rusbyi are the sister group of remaining species of this genus. In this article, we report for the first time Rhamdella aymarae from the Pilcomayo River Basin and extend its distribution to the province of Santiago del Estero. We perform a phylogenetic reconstruction based on mitochondrial marker CO I, which allowed to corroborate the taxonomic assignment of the studied specimens and showed that Rhamdella is not a monophyletic group. This contribution shows evidence that the relationships between genera of the family Heptapteridae require more detailed studies to define their classification.